Internalization of Akhlakul Karimah Values Through a Humanistic Approach to Islamic Religious Education Learning for Generation Z - Sahjad M. Aksan; Alfath Julfi; Muh. Ilham Usman; Eko Nursalim (PT. Anagata Sembagi Education, 2025)
The moral crisis among Generation Z is a serious challenge in the context of 21st-century education, especially amidst the dominance of digital culture that influences their mindset, behavior, and ethical values. This generation grew up in a social environment dominated by value relativism, instant information consumption, and minimal moral role models from the family and community environment. In conditions like this, the normative and cognitive Islamic Religious Education (PAI) learning approach has proven unable to touch the affective and existential dimensions of students. This study uses a literature study method with a qualitative-descriptive approach to explore the relevance and effectiveness of the humanistic approach in internalizing the values of akhlakul karimah. The humanistic approach, which emphasizes respect for personal experience, self-reflection, and empathetic relationships, is considered more capable of bridging religious teachings with students' real lives. Strategies such as experiential learning, contextual teaching and learning (CTL), and value clarification techniques (VCT) are important instruments in presenting transformative and meaningful value education. This study recommends the need for curriculum reform, humanistic teacher training, and a school culture that supports active participation and moral awareness of students. Thus, Islamic Religious Education can be a space for character formation that is not only formally religious, but also socially and spiritually meaningful.